P311Hypertrophic cardiomyopathy and other forms of left ventricular hypertrophy. The P wave can make the difference. (18th June 2020) - Raab, S; Roten, L; Branca, M; Nozica, N; Wilhelm, M; De Marchi, S; Brugger, N; Elchinova, E; Seiler, J; Asatryan, B; Tanner, H; Baldinger, S H; et al.
Abstract: Background: Structural disarray of hypertrophied myocytes and interstitial fibrosis characterize hypertrophic cardiomyopathy (HCM). These morphological changes also affect atrial myocytes and, together with hemodynamic alterations because of HCM, may lead to atrial cardiomyopathy. Purpose: To investigate the incremental value of P-wave parameters to differentiate left ventricular hypertrophy (LVH) because of HCM from LVH in hypertensive heart disease (HHD) and athletes heart. Methods: In a prospective study, we compared electrocardiographic (including signal-averaged ECG of the P wave) and echocardiographic data of patients with HCM, HHD and athletes heart. We developed a predictive model with a simple scoring system to identify HCM. Results: We compared data of 27 patients with HCM (70% males, 49.8 ± 14.5 years), 324 patients with HHD (52% males, 74.8 ± 5.5 years), and 215 subjects with athletes heart (72% males, 42.3 ± 7.5). The table shows the significant differences among the 3 groups. We included the following parameters into a predictive score to differentiate HCM from other forms of LVH: QRS width (>88ms = 1 point), P-wave integral (>688µVs = 1 point) and septum thickness (>12mm = 2 points). A score >2 (Youden index 0.626) correctly classified HCM in 81% of the cases with a sensitivity and specificity of 82% an 81%, respectively. Conclusion Differentiation of HCM from other forms of LVH is improved by including atrial parameters. A simple scoring system including septum thickness, QRS width and P wave integral allowed identification of patients with HCM with a sensitivity and specificity of >80%. This score needs to be validated prospectively.